2011
DOI: 10.1375/twin.14.5.417
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphism in hsa-mir-196a-2 and Breast Cancer Risk: A Case Control Study

Abstract: microRNAs are small, non-coding RNAs that influence gene expression on a post-transcriptional level. They participate in diverse biological pathways and may act as either tumor suppressor genes or oncogenes. As they may have an effect on thousands of target mRNAs, single-nucleotide polymorphisms in microRNA genes might have major functional consequences, because the microRNA's properties and/or maturation may change. miR-196a has been reported to be aberrantly expressed in breast cancer tissue. Additionally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 18 publications
2
26
0
4
Order By: Relevance
“…This was mimicked by another group who found statistically significant association between the T allele and decreased cancer risk (22). However, these results have been disputed by additional studies which found no significant association between the polymorphism and breast cancer risk (23)(24)(25).…”
Section: Polymorphisms Within Mirnasmentioning
confidence: 90%
“…This was mimicked by another group who found statistically significant association between the T allele and decreased cancer risk (22). However, these results have been disputed by additional studies which found no significant association between the polymorphism and breast cancer risk (23)(24)(25).…”
Section: Polymorphisms Within Mirnasmentioning
confidence: 90%
“…Second, the hsa-mir-196a-2 SNP rs11614913 CC genotype has been significantly associated with increased risk for breast, lung and gastric cancers in Chinese populations; conversely, the homozygous TT genotype has been significantly associated with esophageal cancer in non-smoking European males [48]. Based on these results, recent studies have called for more detailed analysis of the frequency of this allele in different ethnic groups [58]. We observed a significantly higher frequency of the hsa-mir-196a-2 C-allele at SNP rs11614913 in African compared to non-African populations (F ST  = 0.41; p < 0.001) (Figure 5D).…”
Section: Discussionmentioning
confidence: 99%
“…The diamond represents the pooled OR and 95% CI. Begg lung cancer [30][31][32][33][34], breast cancer [35][36][37][38][39][40], gastric cancer [41,42], liver cancer [43][44][45][46], gallbladder cancer [47,48], prostate cancer [47,49], esophageal cancer [50][51][52][53], head and neck cancer [54][55][56], cervical cancer [57], and glioma [58]. But the results remain conflicting and conclusive.…”
Section: Discussionmentioning
confidence: 99%